The impact of the National Qualifications Framework on Higher Education with specific reference to access, teaching and learning : a case study - Matentjie, Tshepiso (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil)--University of Stellenbosch, 2005.